THE ASSESSMENT OF STUDENTS’ SPEAKING SKILLS IN INDONESIAN CLASSROOMS - I Nyoman Suwandi (International Journal of Social Science, 2023)
Speaking is one of the most important language skills to be mastered. Speaking is a person's ability to express or express ideas and thoughts within oneself that involve others in conveying this information using words. This research examined the assessment practiced by the teachers in assessing speaking skills. This research method is a qualitative method where the data were analyzed critically and presented descriptively. Data required for this study were collected through interviews and classroom observations. This study found that teachers conducted various assessments to assess students’ speaking skills. Assessment becomes highly powerful tool in improving the quality of learning. Consequently, careful considerations should be taken into account to carry out valid and reliable assessment. This study implies that teachers should always consider the appropriate assessment to be carried out in the classroom to measure the students’ speaking skills and use the results for learning and teaching improvement